2022
DOI: 10.1002/jmor.21472
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the American alligator (Alligator mississippiensis) prenatal head: A morphometric approach

Abstract: Variation in vertebrate cranial morphology is both extensive and functionally significant. Morphometric analysis attempts to explain such variation in form in evolutionary and functional contexts. Developmental morphometric analyses of vertebrate crania are less common, and many taxa are underrepresented. For | 805

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Simple linear growth patterns are observed when considering only individual measurements (Deeming & Ferguson, 1990; Peterka et al, 2010). A recent study showed a phasic morphometric modular development in alligator embryo growth, with a middle phase of reduced nasal growth encompassing stages 16–20 breaking an otherwise linear head growth pattern (Beeching et al, 2022). This phase corresponds roughly to the growth and the development of the secondary palate (Ferguson, 1985), the NLD and the facial bones (this study).…”
Section: Discussionmentioning
confidence: 99%
“…Simple linear growth patterns are observed when considering only individual measurements (Deeming & Ferguson, 1990; Peterka et al, 2010). A recent study showed a phasic morphometric modular development in alligator embryo growth, with a middle phase of reduced nasal growth encompassing stages 16–20 breaking an otherwise linear head growth pattern (Beeching et al, 2022). This phase corresponds roughly to the growth and the development of the secondary palate (Ferguson, 1985), the NLD and the facial bones (this study).…”
Section: Discussionmentioning
confidence: 99%